PENGARUH EDUKASI GIZI DENGAN MEDIA BOOKLET TERHADAP TINGKAT PENGETAHUAN, SIKAP, TINGKAT KONSUMSI, DAN BERAT BADAN PADA REMAJA DENGAN OVERWEIGHT DI BIMBINGAN BHC WONOREJO- JEMBER - Mayrhanitha, Athalia Mayrhanitha; Soelistyorini, Dwie; Luthfiyah, Fifi (Poltekkes Kemenkes Malang, 2025)
The purpose of this study was to determine the effect of nutrition education with booklet media on the level of knowledge, attitudes, energy consumption levels and nutrients (protein, fat, and carbohydrates), and body weight of adolescents with overweight in BHC Wonorejo - Jember tutoring. This type of research is a quasy experiment, with a one-group pre-post-test design. The results of this study are that there is an effect of nutrition education through booklet media on overweight adolescents on the level of knowledge with a significance value of Sig. (2-tailed) = 0.001 <0.05. There is an effect of nutrition education through booklet media on overweight adolescents on attitudes with a significance value of Sig. (2-tailed) = 0.001 <0.05. There is an effect of nutrition education through booklet media on overweight adolescents on the level of energy consumption, protein, and fat, and there is no effect of education on the level of carbohydrate consumption. There is an effect of nutrition education through booklet media on overweight adolescents on body weight with a significance value of Sig.( 2-tailed ) = 0.003 <0.05.